If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -8y = 12 Solving -7x + -8y = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8y' to each side of the equation. -7x + -8y + 8y = 12 + 8y Combine like terms: -8y + 8y = 0 -7x + 0 = 12 + 8y -7x = 12 + 8y Divide each side by '-7'. x = -1.714285714 + -1.142857143y Simplifying x = -1.714285714 + -1.142857143y
| 0=-4 | | 4-4b=8(8+2b) | | x^2-(4p+1)x+(5p^2+2p)=0 | | y=296+7x | | y=7x+296 | | 3(w-2)+7=1-3w | | 4+v=3v-8 | | X=2(0) | | (-5)-(-2)=g+4 | | -60=6x-5y | | 34:4= | | -3(12-6x)=7(8-2x) | | (-35)=c+(-18) | | 5x+13=3x-93 | | X=2-2 | | $45.00-30%= | | -3(m-7)=2m-4 | | 7x+2+2+3+8=180 | | -3x=x-20 | | 3x+5y=328 | | (-9)=b+(-13) | | 13=-6+2x | | 4u-8=5(4-u)-1 | | 13=6-2x | | A-4=(-5) | | 10y-2x=50 | | 6x+12+2x+60=90 | | -12.7+-4.4=x | | K+(-6)=4 | | -3x-3+9x+7-x=29 | | -3x-3+9x+7x-x=29 | | (6x-w)(7x+w)= |